وعدة الوي الصالح سيدي علي بن خزان بالدبيلة بين الاحتفال الشعبي والأداء الطقوسي - غريبي, محمد الساسي; ليفة, بلال (University of Eloued جامعة الوادي, 2024)
Abstract The study of popular literature is shedding light on cultural history, and the basic entrance to understanding the current culture and the existing social structure, and in this context, which views popular literature as the mirror that reflects the true picture of the life of a society, this research comes tagged with: “ El_waada of , SIDI ALI BEN KHAZZEN in Dabila between popular celebration and ritual performance”. This study deals with the study of the Kabylie region between the religious symbols in DEBILA and the social religious behaviors therein, through the practices we do in EL-WAADA OF SIDI ALI BEN KHAZZEN between their appearance in popular ceremonies and their ritual performance, with the aim of monitoring this phenomenon and exploring its details and effects clearly. It is transparent in that it and the secrets of society are attached to it despite the disappearance of many other traditions and ceremonial bows, in addition to examining how the popular imagination draws the image of this righteous guardian in the mind of the group. This study concludes that: In EL_WAADA OF SIDI ALI BEN KHAZZEN, in DEBILA, the ritual performance meets the popular celebration in that they are the material expression of an internal belief collectively, characterized by repetition, organization, and symbolism. Thus, the promise becomes a cultural, social, and historical indicator that reflects the way individuals and groups think, and even the way they think. Their lives and their perception of life. إن دارﺳـــﺔ اﻷدب اﻟـــﻌﻲ ﻫـــﻲ ﺎـــﺔ ﺗـــﻠ اﻟـــء ﻋﻠـــﻰ اﻟـــﺎرﺦ اﻟﻘـــﺎﻓﻲ ، واﻟـــﺧﻞ اﻷﺳﺎﺳــﻲ ﻟﻔﻬــ اﻟﻘﺎﻓــﺔ اﻟﺎﻟــﺔ واﻟــﺎء اﻻﺟــﺎﻋﻲ اﻟﻘــﺎﺋ، وﻓــﻲ ﻫــا اﻟــﺎق اﻟــ ﯾــ ﻟــﻸدب اﻟﻌﻲ ﻋﻠﻰ أﻧﻪ اﻟآة اﻟﻲ ﺗﻌ اﻟرة اﻟﺔ ﻟـﺎة ﻣـﻊ ﻣـ اﻟﻌـﺎت ـﺄﺗﻲ ﻫـا اﻟ اﻟﺳم ﺑـ": وﻋـة اﻟـﻟﻲ اﻟـﺎﻟﺢ ﺳـ ﻋﻠـﻲ ﺑـ ﺧـان ﺎﻟﺑﻠـﺔ ﺑـ اﻻﺣﻔـﺎل اﻟـﻌﻲ واﻷداء اﻟﻘﺳﻲ". وﺗﻌـــﺎﻟﺞ ﻫـــﻩ اﻟارﺳـــﺔ ﺗﻠـــ اﻟﻌﻼﻗـــﺔ ﺑـــ اﻟﻣـــز اﻟﯾـــﺔ ﻓـــﻲ ﻣﻘـــﺔ اﻟﺑﻠـــﺔ واﻟـــﻠﺎت اﻻﺟﺎــﺔ اﻟﯾــﺔ ﻓﻬــﺎ ﻣــ ﻣﺎرﺳــﺎت ﻓــﻲ وﻋــة اﻟــﻟﻲ اﻟــﺎﻟﺢ ﺳــ ، ﻣــ ﺧــﻼل ﻣــﺎ ــ ﻋﻠـﻲ ﺑـ ﺧــان ﺑـ ﻣﻬﻫـﺎ اﻻﺣﻔــﺎﻟﻲ اﻟـﻌﻲ وأداﺋﻬــﺎ اﻟﻘﺳـﻲ، ﻐـض رﺻــ ﻫـﻩ اﻟــﺎﻫة واﻟﻘـــ ﻋـــ ﺟﺋﺎﺗﻬـــﺎ وآﺛﺎرﻫـــﺎ ـــﻞ ﻋﻠـــﻲ، واﻟـــ ﻓـــﻲ أﺳـــﺎب اﺳـــارﻫﺎ وأﺳـــار ﺗﻌﻠـــ ،اﻟﻊ ﺑﻬﺎ ﻋﻠﻰ اﻟﻏ ﻣ اﻧﺛﺎر اﻟـ ﻣـ اﻟﻌـﺎدات واﻟﻘﺎﻟـ واﻟﻘـس اﻻﺣﻔﺎﻟـﺔ اﻷﺧـ إﻟـــﻰ ﺟﺎﻧـــ اﻟﻗـــف ﻋﻠـــﻰ ـــﺔ رﺳـــ اﻟـــﻞ اﻟـــﻌﻲ ﺻـــ رة ﻫـــا اﻟـــﻟﻲ اﻟـــﺎﻟﺢ ﻓـــﻲ ذﻫـــ اﻟﺎﻋﺔ. وﺗﻠــ ﻫــﻩ اﻟارﺳــﺔ إﻟـــﻰ أن: ﻓــﻲ وﻋــة اﻟـــﻟﻲ اﻟــﺎﻟﺢ ﺳــ ﻋﻠـــﻲ ﺑــ ﺧــان ﺎﻟﺑﻠـــﺔ ﯾﻠﻘﻲ اﻷداء اﻟﻘﺳـﻲ ﻣـﻊ اﻻﺣﻔـﺎل اﻟـﻌﻲ ﻓـﻲ ﻧﻬـﺎ اﻟﻌـ اﻟـﺎد ﻟﻌﻘـ داﺧﻠـﻲ ـﻞ ﺟـــﺎﻋﻲ، ﯾـــ ـــﺎﻟار واﻟـــ واﻟﻣـــﺔ، وـــﻟ ﺗـــﺢ اﻟﻋـــة ﻣﺷـــا ﺛﻘﺎـــﺔ واﺟﺎـــﺎ وﺗﺎرﺎ ﻌ ﻘﺔ ﺗﻔ اﻷﻓاد واﻟﺎﻋﺎت ﺑﻞ وﺣﻰ ﻘﺔ ﻬ وﺗرﻫ ﻟﻠﺎة.
أدب شعبي
Keywords: EL_WAADA; SIDI ALI BEN KHAZZEN; DEBILA; popular celebration; ritual performance.